Digital Literacy Challenges in Livestock Micro-Entrepreneurship: A Rapid Qualitative Study in Kuningan, Indonesia - Misbachudin Misbachudin (Politeknik Siber Cerdika Internasional, 2025)
Backround: Despite increasing smartphone penetration in rural Indonesia, livestock micro-entrepreneurs face persistent challenges in leveraging digital technologies for business development, creating critical gaps between technology access and functional digital literacy that constrain economic opportunities.Objective: This study investigates digital literacy challenges among livestock micro-entrepreneurs in Kuningan, Indonesia, examining capability deficits, underlying barriers, and business consequences to inform targeted intervention design.Method: A rapid qualitative research design was employed over three months, conducting in-depth semi-structured interviews with 18 purposively-sampled livestock micro-entrepreneurs (poultry and cattle farmers) representing diverse demographics. Data collection integrated interviews, direct observation of smartphone usage, and literature review, analyzed through thematic analysis identifying patterns of digital literacy challenges and barrier categories.Findings and Implications: Despite universal smartphone ownership, participants exhibited profound deficits across four dimensions: operational skills (88.9% lacked file management understanding), informational literacy (88.9% never checked online prices before selling), strategic competency (100% showed no proactive customer engagement), and safety awareness (94.4% vulnerable to phishing). These gaps emerged from intersecting factors including age, education, gender opportunity structures, training absence, and infrastructural constraints.Conclusion: Business consequences included 18-27% revenue losses from intermediary dependency, preventable livestock mortality, and financial exclusion imposing higher lending costs. Digital literacy deficits impose substantial economic penalties that far exceed intervention costs. Effective inclusion requires multifaceted approaches addressing not just skills but also psychological barriers, institutional support systems, and infrastructural limitations.